Physical studies of sugar-based surfactants / Seyed Mohammad Mirzadeh Hosseini - Seyed Mohammad Mirzadeh, Hosseini (2017)
Phospholipids are widely used to produce delivery systems for the entrapment and release of drugs from vesicles, also called liposomes, especially for chemotherapy. The replacement of ionic phospholipids with non-ionic glycolipids may help to improve the stability of drug carriers due to stronger molecular interactions. However, the synthetic challenge for highly pure glycolipids in combination with the vast structural diversity of carbohydrates makes a random testing of sugar head-groups for the optimization of vesicle stability highly inefficient. On the other hand, computational methods may be used to predict detailed interactions of the surfactants. However, this method requires experimental validation. Of particular interest is hydrogen bonding within the hydrophilic sugar head-group region. Unfortunately the intermolecular hydrogen bonding between surfactants is difficult to measure. Instead, the validation of computational results can focus on the interaction of the surfactants with water. This study aims to determine the bound water content of glycolipids in the lamellar phase, which is a good approximation for vesicular assemblies. In this regard, several glycolipid molecules were synthesised and investigated. The bound water content was examined by deuterium NMR (2H-NMR) and differential scanning calorimetry (DSC). In the latter the melting enthalpy of free water was measured to indirectly determine the bound water content. These experimental results are compared with computational studies, which model the slightly curved vesicle bilayer as a multilayer analogue of the lamellar phase. The complexity of carbohydrate stereochemistry and their hydrogen bonding is very intriguing, and minor changes in orientation can cause significant effects on the self-assembly. With respect to this, the stereo chemical effect of anomers and epimers on the self-assembly of Guerbet glycosides was investigated. The comparison of phase transition temperatures revealed a cis-trans correlation of anomeric-epimeric pairs based on glucose and galactose, which can be explained by the direction of hydrogen bonding of the hydroxyl group at the epimeric C-4 carbon.